Association of tobacco use and cessation with coronary atherosclerosis. (February 2017) - Cheezum, Michael K.; Kim, Alexander; Bittencourt, Marcio S.; Kassop, David; Nissen, Alexander; Thomas, Dustin M.; Nguyen, Binh; Glynn, Robert J.; Shah, Nishant R.; Villines, Todd C.
Abstract: Background and aims: The impact of tobacco use and cessation on atherogenesis remains unclear. We aimed to study the association of tobacco use and prior cessation with the presence, extent and severity of atherosclerosis on coronary computed tomographic angiography (CTA). Methods: We examined 1798 consecutive symptomatic patients without known coronary artery disease (CAD) referred for CTA, stratified by smoking status (never, current [within 30 days], or former [>30 days before CTA]). Plaque severity (none, <50%, ≥50% stenosis), composition (non-calcified [NCP], partially calcified [PCP], or calcified plaque [CP]), and segment involvement score (SIS) were visually graded. Multivariate analysis was performed, adjusting for CAD risk factors and cholesterol lowering medication use. Results: The median age of patients was 50 years [IQR:42–58] (61% male), with 74% never smokers, 12% current smokers, and 14% former smokers (median quit duration = 12 years [IQR:3–26]). Smoking exposure in former versus current smokers was 11 [IQR:5–25] and 10 [IQR:2–20] pack-years, respectively ( p = 0.01). Compared to never smokers, current smokers demonstrated an increased odds ratio of all plaque types (adjusted OR: any NCP = 1.55 [95% CI 1.04–2.32], p = 0.03; any PCP = 1.61 [1.10–2.37], p = 0.02; any CP = 1.93 [1.32–2.81], p = 0.001), non-obstructive CAD (aOR = 1.47 [1.04, 2.07], p = 0.03), obstructive CAD (aOR = 1.81 [1.01–3.24], p = 0.047), and SIS > 4 (aOR = 1.60 [1.04–2.46], p = 0.03). Compared to current smoking, prior smoking cessation (≥12 years) was associated with a decreased odds ratio of any NCP (aOR = 0.42 [0.19–0.90], p = 0.03), CP (aOR = 0.43 [0.22–0.84], p = 0.02), and obstructive CAD (aOR = 0.40, [0.15–0.98], p = 0.048). Conclusions: Current smoking is independently associated with the presence and extent of coronary plaque, and a higher risk of non-obstructive and obstructive CAD compared to never smoking. Prior smoking cessation correlated with improvements in CTA-identified plaque measures. Highlights: Current smokers demonstrated an increase in coronary artery disease (CAD) extent and severity vs. never smokers. Ever smokers had a dose-dependent association with the presence and extent of CAD. Smoking cessation correlated with improved plaque measures vs. current smoking.